Factors associated with adverse clinical outcomes among obstetrics trainees. Issue 7 (July 2015) - Aiken, Catherine E; Aiken, Abigail R; Park, Hannah; Brockelsby, Jeremy C; Prentice, Andrew
<x xml:space="preserve">Abstract</x> Objectives This study was conducted to determine whether UK obstetrics trainees transitioning from directly to indirectly supervised practice have a higher likelihood of recording adverse patient outcomes in operative deliveries compared with other indirectly supervised trainees, and to examine whether performing more procedures under direct supervision is associated with fewer adverse outcomes in initial practice under indirect supervision. Methods We examined all deliveries (13 856) conducted by obstetricians at a single centre over 6 years (2008–2013). Mixed‐effects logistic regression models were used to compare estimated blood loss (EBL), maternal trauma, umbilical arterial pH, delayed neonatal respiration, failed instrumental delivery, and critical incidents for trainees in their first indirectly supervised year with those for trainees in all other years of indirect supervision. Outcomes for trainees in their first indirectly supervised 3 months were compared with their outcomes for the remainder of the year. Linear regression was used to examine the relationship between number of procedures performed under direct supervision and initial outcomes under indirect supervision. Results Trainees in their first indirectly supervised year had a higher likelihood of recording EBL of > 2 L at any delivery (odds ratio [OR] 1.32, 95% confidence interval [CI] 1.01–1.64; p < 0.05) and of failed instrumental delivery (OR 2.33, 95% CI 1.37–3.29; p < 0.05) compared with other indirectly supervised trainees. Other measured outcomes showed no significant differences. In the first 3 months of indirect supervision, the likelihood of operative vaginal deliveries with EBL of > 1 L (OR 2.54, 95% CI 1.88–3.20; p < 0.05) was higher than in the remainder of the first year. Performing more deliveries under direct supervision prior to beginning indirectly supervised training was associated with decreased risk for recording EBL of > 1 L (p < 0.05). Conclusions Obstetrics trainees in their first year of indirectly supervised practice have a higher likelihood of recording immediate adverse delivery outcomes, which are primarily maternal rather than neonatal. Undertaking more directly supervised procedures prior to transitioning to indirectly supervised practice may reduce adverse outcomes, which suggests that experience is a key consideration in obstetrics training programme design.